Monetizing Crime: Public Perception and The Stigma of Commercialized Justice in Indonesian Penal Mediation - Kholid Zulfa; Nurus Zaman; Mohd Zaidi Daud; Hanif Nur Rokhim; Nur Hayati Aulia (UIN Sunan Kalijaga Yogyakarta, 2026)
This article examines the stigmatization of penal mediation in Indonesia as a form of commercialized justice or monetization of crime, particularly in the context of the newly enacted National Criminal Code of 2023. Utilizing normative legal research methods incorporating conceptual and statutory approaches, this study analyzes the factors shaping public perception that penal mediation constitutes a commodification of justice. The findings identify three primary sources of this stigma: (1) the persistence of retributive paradigms within public legal consciousness; (2) the absence of comprehensive technical regulations governing penal mediation implementation; and (3) economic disparities that undermine the bargaining position of economically disadvantaged parties. The research further reveals a significant disjuncture between the formal provisions of the National Criminal Code and their practical implementation across Indonesian jurisdictions, attributable to inadequate facilitator training, insufficient oversight mechanisms, and the lack of standardized procedural guidelines. Conceptually, penal mediation embodies restorative justice principles centered on victim restoration, offender accountability, and social reintegration, rather than constituting a marketplace for justice. This study contributes to restorative justice scholarship by integrating John Rawls' theory of justice with Islamic legal principles, offering a culturally grounded framework for analyzing equitable access to restorative processes. The findings inform policy recommendations encompassing comprehensive technical regulations, transparent oversight mechanisms, professional and independent facilitators, equitable legal aid provision, and sustained public education initiatives to ensure penal mediation functions as an instrument of substantive justice rather than a vehicle for commercializing crime.